Testing for SARS-CoV-2 (COVID-19): a systematic review and clinical guide to molecular and serological in-vitro diagnostic assays. Issue 3 (September 2020) - La Marca, Antonio; Capuzzo, Martina; Paglia, Tiziana; Roli, Laura; Trenti, Tommaso; Nelson, Scott M.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its associated coronavirus disease 2019 (COVID-19) pandemic has demanded rapid upscaling of in-vitro diagnostic assays to enable mass screening and testing of high-risk groups, and simultaneous ascertainment of robust data on past SARS-CoV-2 exposure at an individual and a population level. To meet the exponential demand in testing, there has been an accelerated development of both molecular and serological assays across a plethora of platforms. The present review discusses the current literature on these modalities, including nucleic acid amplification tests, direct viral antigen tests and the rapidly expanding laboratory-based and point of care serological tests. This suite of complementary tests will inform crucial decisions by healthcare providers and policy makers, and understanding their strengths and limitations will be critical to their judicious application for the development of algorithmic approaches to treatment and public health strategies.